Discourse, resistance and organization. Critical discourse analysis of the 'revolt of the humanities' in Poland. Issue 3 (4th May 2022) - Stankiewicz, Łukasz
ABSTRACT: In the recent decade Polish universities have undergone a series of reforms limiting their independence from the state. This provoked protests from the humanities faculty and led to establishing organizations that actively opposed the reform. The purpose of this paper is to present a critical discourse analysis (CDA) of press articles describing a process of organizing resistance to the reform of the higher education and science system in Poland. The 'revolt of the humanities' is examined in the perspective of Bob Jessop's theory of social crises. The outcome of the study is a description of the discursive reduction of the complexity of political actors' demands. The result of complexity reduction was creation of a better organized and more politically effective forms of opposition to the reform agenda.